Mitochondria–Lysosome Crosstalk: From Physiology to Neurodegeneration. Issue 1 (January 2020) - Deus, Cláudia M.; Yambire, King Faisal; Oliveira, Paulo J.; Raimundo, Nuno
Abstract : Cellular function requires coordination between different organelles and metabolic cues. Mitochondria and lysosomes are essential for cellular metabolism as major contributors of chemical energy and building blocks. It is therefore pivotal for cellular function to coordinate the metabolic roles of mitochondria and lysosomes. However, these organelles do more than metabolism, given their function as fundamental signaling platforms in the cell that regulate many key processes such as autophagy, proliferation, and cell death. Mechanisms of crosstalk between mitochondria and lysosomes are discussed, both under physiological conditions and in diseases that affect these organelles. Highlights: The functions of mitochondria and lysosomes are coordinated with cellular metabolism and signaling. AMPK and mTORC1 mediate mitochondria–lysosome crosstalk. Acute and chronic mitochondrial stress has opposite effects on lysosomal biogenesis. Lysosomal storage diseases trigger repression of mitochondrial biogenesis. Mitochondria–lysosome crosstalk is impaired in neurodegenerative diseases.